"Homophobia hurts": Mourning as resistance to violence in South Africa. Issue 2 (3rd April 2017) - Moreau, Julie
ABSTRACT: Much has been written on the successful lesbian, gay, bisexual, transgender, and intersex movement in South Africa, and the resulting institutionalization of sexual minority rights. Comparatively less has been written about the forms of activism undertaken specifically by Black lesbians that are not oriented toward legal change. In this article, I assert the need to examine public demonstrations of mourning as an act of Black lesbian resistance to violence in South Africa. Based on in-depth interviews with members of Free Gender, a Black lesbian organization, I argue that members' conceptualizations of mourning as providing community support force a reconsideration of what it means to be human. In order to grasp the decolonial potential of Free Gender's activism, I draw on Sylvia Wynter's argument that a singular Western bourgeois conception of human has come to dominate globally.